2010
DOI: 10.1007/s00535-010-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotropic HCV strain can infect human primary naïve CD4+ cells and affect their proliferation and IFN-γ secretion activity

Abstract: Background Lymphotropic hepatitis C virus (HCV) infection of B and T cells might play an important role in the pathogenesis of hepatitis C. Recently, we showed that a lymphotropic HCV (SB strain) could infect established T-cell lines and B-cell lines. However, whether HCV replication interferes with cell proliferation and function in primary T lymphocytes is still unclear. Aim The aim of this study was to analyze whether HCV replication in primary T lymphocytes affected their development, proliferation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…However, the antiviral activity of 25(OH) vitamin D3 is not so remarkable. Moreover, the system of HCV replication in that study did not include the immune cells that are important for the control of HCV replication [32][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the antiviral activity of 25(OH) vitamin D3 is not so remarkable. Moreover, the system of HCV replication in that study did not include the immune cells that are important for the control of HCV replication [32][35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the capacity of culture-produced HCV from a different genotype (2a) to infect PBMC has been challenged [52], it has also been shown that HCV from the same genotype as the one used in this manuscript (1a) [51] infects primary CD4+ T cells. HCV-Core could also enter CD4+ T cells as it has previously been suggested [23], [40], [53] and data showing that HCV-core protein is present in hepatocytes[54], non-parenchymal liver cells including lymphocytes [55] and in the serum of infected patients [56], together with data showing that it can enter hepatoma cell lines [57] further reinforces such an hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our in vitro clearance and rebound study was a first step toward demonstrating that PSI-352938 was capable of clearing HCV RNA. It is possible that the outcome from an in vivo situation could be different from the results of in vitro studies, especially since HCV could infect organs other than the liver, such as the lymphatic system (24).…”
Section: Discussionmentioning
confidence: 99%